2015
DOI: 10.3389/fmicb.2015.00483
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in-feed administration and withdrawal of tylosin phosphate on antibiotic resistance in enterococci isolated from feedlot steers

Abstract: Tylosin phosphate is a macrolide commonly administered to cattle in North America for the control of liver abscesses. This study investigated the effect of in-feed administration of tylosin phosphate to cattle at subtherapeutic levels and its subsequent withdrawal on macrolide resistance using enterococci as an indicator bacterium. Fecal samples were collected from steers that received no antibiotics and steers administered tylosin phosphate (11 ppm) in-feed for 197 days and withdrawn 28 days before slaughter.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
64
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 46 publications
12
64
2
Order By: Relevance
“…The assembled tree was consistent with the PFGE profile dendrogram observed from our previous study [10]. As expected, clustering was observed for genomes of the same species further verifying the identity of each species based on previous groES-EL spacer speciation [10].
Fig.
…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The assembled tree was consistent with the PFGE profile dendrogram observed from our previous study [10]. As expected, clustering was observed for genomes of the same species further verifying the identity of each species based on previous groES-EL spacer speciation [10].
Fig.
…”
Section: Resultssupporting
confidence: 89%
“…isolated from bovine feces including E. hirae ( n  = 10), E. faecium ( n  = 3), E. villorum ( n  = 2), E. casseliflavus ( n  = 2), E. faecalis ( n  = 1), E. durans ( n  = 1), E. gallinarum ( n  = 1) and E. thailandicus ( n  = 1) were selected for whole genome sequencing (Table 1). These were selected from an archive of isolates collected between 2004 and 2005, which were previously characterized by PFGE and antimicrobial susceptibility testing [10]. At least one representative of each species isolated from bovine feces was selected, and for E. hirae and E. faecium , selection was based on maximizing diversity as measured by PFGE profiles as well as selecting isolates that displayed unique antimicrobial resistance profiles.…”
Section: Methodsmentioning
confidence: 99%
“…Another study found that sub-therapeutic tylosin treatment (Tylan, Elanco; 11 mg/kg in-feed) increased the frequency of Enterococcus spp. harboring erm (B) and/or msrC (a macrolide/streptogramin efflux pump gene) [171]. The authors of that study concluded that the diversity of Enterococcus decreased in the period between when cattle entered and exited the feedlot, and that the AMR Enteroccocus were derived from strains present in the intestinal microbiota before tylosin administration [171].…”
Section: Antimicrobials and The Bovine Microbiotamentioning
confidence: 99%
“…Additionally, a study by Meyer et al () studied the effects of essential oils as alternatives which tended to reduce liver abscesses in comparison with the control animals, though not significantly ( P > 0·05). Beukers et al () suggested that early withdrawal of tylosin prior to slaughter contributed to a lower proportion of macrolide‐resistant enterococci. Additionally, Müller et al () noted that the environment where cattle are raised, namely where antibiotics have previously been used, seemed to play a large role in the presence of macrolide‐resistant enterococci.…”
Section: Introductionmentioning
confidence: 99%